Of mice and coyotes: mammalian responses to rangeland management practices in tallgrass prairie - Ricketts, Andrew Michael (Kansas State University, 2016)
Habitat heterogeneity is a key driver of biodiversity in many ecosystems. In native ecosystems, habitat heterogeneity can arise from multiple drivers including nutrients, topoedaphic conditions, and ecological disturbance. Historically, the prairies of North America existed as a heterogeneous mosaic of habitat conditions created by the interaction of fire and grazing by native ungulates. The focus of many grazing systems has been to minimize disturbance caused by grazing by promoting uniform distributions of grazing animals across management units. Patch-burn grazing is an alternative rangeland management practice that has been proposed to restore historical patch dynamics and biodiversity to rangelands by simulating historical disturbance processes. In my dissertation research, I tested the hypothesis that patch- burn grazing restores habitat heterogeneity to rangelands, and that the resulting habitat heterogeneity can promote biodiversity of native wildlife. I focus on responses of small mammals and coyotes to patch-burn grazing to gain a better understanding of wildlife responses to rangeland management, and because grassland mammals are an ecologically important group. My 3.5-year field study of habitat and small mammal responses to rangeland management showed that: 1) patch-burn grazing created greater heterogeneity in vegetative structure and composition of plant functional groups than in positive and negative controls; 2) habitat heterogeneity created by the interaction of fire and grazing increased small mammal richness and diversity compared to a negative control managed for uniform grazing distributions; 3) the interaction of fire and grazing structured small mammal communities in tallgrass prairie; and 4) population dynamic responses of small mammals to fire and grazing disturbance were species- specific. My 3-year study of coyote survival and resource selection revealed that: 1) rangeland management influences resource selection by coyotes in seasons when they depend on small mammal prey, but not during other seasons; and 2) anthropogenic sources of mortality are important for coyotes at a protected area, even in the absence of harvest. My field results show that restoring the drivers of historical patch dynamics to managed rangelands and publicly held grasslands that are not currently grazed could have profound effects on biodiversity conservation in North America, while continuing to provide ecosystem services to society.
Keywords: Fire; Grazing; Habitat heterogeneity; Pyric herbivory; Small mammal; Coyote